A national strategic plan for reducing the burden of sexually transmitted infections in Israel by the year 2025 - Daniel Chemtob; Dan Gandacu; Zohar Mor; Itamar Grotto; Emilia Anis; Elliot Rosenberg (BMC, 2017)
Abstract Background There is on ongoing debate in the literature regarding the real burden of STIs (sexually transmitted infections) in Western countries and the proper strategies needed to estimate and to prevent them. Our purpose is to present an evidence-based national strategic plan for STI prevention in Israel through assessing the current burden of illness, leading international preventive strategies, and practical policymaking experience. Methods Epidemiologic and health policy data on STIs were analyzed from various sources: a) systematic national surveillance data for the years 2002-2014; b) the international scientific literature (published between 2002-16; keywords: Sexually Transmitted Diseases (STD) (or STI) AND prevention AND intervention AND gonorrhea OR chlamydia OR syphilis; c) internal Ministry of Health (MOH) analyses and reports, and d) expert opinion. Results Incidence rates in Israel of Chlamydia trachomatis (chlamydia), Neisseria gonorrhea (gonorrhea) and Treponema pallidum (syphilis) are lower than in most Western countries. However, rates vary among population subgroups: chlamydia, gonorrhea and syphilis are higher in Jews than in non-Jews, and this gap has increased for chlamydia over the past decade. Primary and secondary syphilis rates have increased among men having sex with men (MSM). It is likely that STIs are under-reported and that incidence is even rising due to migration. A key recommendation is the establishment of an active surveillance system of STIs, utilizing active case finding in high risk populations, along with regular contact with STI clinics run by the four national health management organizations and by the MoH. As with most European countries, the low prevalence of chlamydia and gonorrhea does not justify population-wide screening. Conversely, the increasing incidence of syphilis among MSM should lead to regular screening among this group. Conclusions A national STIs prevention strategy for the year 2025 was presented. Although the current burden of illness is low relatively to other Western countries, this is thought to reflect a certain degree of underreporting. These and other gaps suggest a need for focused epidemiologic and health services research to better characterize health risk behaviors as well as provider practice patterns. Innovative implementation strategies have been described, together with the capacity building components needed for developing specific and implementable policy recommendations for the year 2025.